An Epidemiological Study Incidence Rates of Risk Factors for Colorectal Cancer's Early Symptoms in the Community in Gondanglegi District, Malang, East Java, Indonesia: An Epidemiological Study - Djoko Heri Hermanto; Nina Nurarifah; Herwindo Pudjo Brahmantyo; Nadia Alfiani; Naya Adi Dharmesta; Putri Ardiyanti; Arif Qhadafy; Shinta Oktya Wardhani (Masters Program in Public Health, 2024)
Background: Colorectal cancer (CRC) is one of the most common types of cancer worldwide. CRC is most typical symptom is hematochezia while the risk factors encompass sex, age, genetic predispositions, history of colorectal polyps or cancer, chronic inflammatory bowel diseases, physical exercise, and specific dietary choices, including high red meat intake, fried food, and low fiber consumption. This study aims to screen the risk factors of colorectal cancer.Subjects and Method: This research was conducted on residents in the Sepanjang village, Malang Regency, involved in community service by the Internist Association of Malang. Community service was carried out in July 2023 and 148 residents were involved in collecting data on risk factors for colorectal carcinoma. Data collection was carried out using a questionnaire with a cross-sectional approach. The questionnaire assesses the presence of symptoms of bloody stools and several habits related to colorectal carcinoma risk factors, including age, gender, exercise routine, and dietary history. Data presentation and analysis were carried out as in the table.Results: Among the risk factors listed assessed using the questionnaire, Men (p=0.021), lack of exercise (p= 0.008), consumption of fried food (p= 0.021), and consumption of instant noodles (p= 0.013) significantly affect the prevalence of hematochezia.Conclusion: Men, lack of exercise, consumption of fried food, and consumption of instant noodles significantly affect the hematochezia indicating CRC.